Structure in a sea of sand: fish abundance in relation to man-made structures in the North Sea. (26th October 2018) - Wright, Serena R; Lynam, Christopher P; Righton, David A; Metcalfe, Julian; Hunter, Ewan; Riley, Ainsley; Garcia, Luz; Posen, Paulette; Hyder, Kieran
Abstract: Artificial structures in the marine environment may have direct and/or indirect impact on the behaviour and space use of mobile foragers. This study explores whether environmental and physical features in the North Sea—including artificial structures (wrecks, wind turbines, cables, and oil and gas structures) were associated with local abundance of three fish species: cod ( Gadus morhua ), plaice ( Pleuronectes platessa ), and thornback ray ( Raja clavata ). Generalized additive models (GAMs) were used to compare distributions between data collected by fisheries surveys and electronic tags. Distributions of cod, plaice, and ray were correlated with environmental variables including temperature, depth, and substrate, matching findings from previous studies. All species showed seasonal increases in their abundance in areas with high densities of artificial structures, including oil and gas platforms and wrecks. Independent of whether fish purposefully associate with these features or whether structures happen to coincide with locations frequented by these populations, the strong association suggests that greater consideration needs to be given to regulation of habitat alterations, including decommissioning.